The UNESCO : IBE Education Thesaurus. First Edition. A Faceted List of Terms For Indexing and Retrieving Documents and Data in the Field of Education; With French Equivalents (UNIPUB, Inc, 1973)
This thesaurus is a list of descriptors and identifiers for the international indexing and retrieving of documents and data in the field of education. The descriptors are placed in seven broad fields; context terms, administration and research terms, instructional terms, people, growing and learning, content, and things. The terms of each field are then placed in facets and sub-facets; i.e., groups which cover related concepts. The seven fields are numbered respectively from 100 to 700. The identifiers--the names of places, institutions, persons--are placed in the 8th field. The second and third digits give a ready serial numbering of the facets. The Thesaurus shows: 1) general headings for fields, facets and sub-facets, 2) alphabetical array of descriptors, 3) alphabetical array of identifiers, and 4) faceted array of descriptors and identifiers. Each English language descriptor is followed by its French equivalent. (CH)